Composition of Algal Oil and Its Potential as Biofuel. (9th April 2012) - Schlagermann, Pascal; Göttlicher, Gerold; Dillschneider, Robert; Rosello-Sastre, Rosa; Posten, Clemens
Abstract : First test flights using blends with algae oil are already carried out and expectations by the aviation and other industries are high. On the other hand technical data about performance of cultivation systems, downstream processing, and suitability of algae oil as fuel are still limited. The existing microalgae growing industry mainly produces for the food and feed market. Energy efficiency is so far out of scope but needs to be taken into account if the product changes to biofuel. Energy and CO2 balances are used to estimate the potential of algae oil to fulfil the EU sustainability criteria for biofuels. The analysis is supported by lab tests as well as data gained by a pilot scale demonstrator combined with published data for well-known established processes. The algae oil composition is indicator of suitability as fuel as well as for economic viability. Approaches attaining high value fractions are therefore of great importance and will be discussed in order to determine the most intended market.